Selfie in student environment: from selfie addiction awareness to everyday practices study - Olga V. Popova, Elena V. Martynenko, Nikolay G. Kutlin, Natalia T. Kolesnik, Irina V. Vologdina, Isita V. Muskhanova, Svetlana A. Knyazev (Opción, 2020)
The relevance of this article is to study such a social phenomenon as selfie. With the development of society, the life of each person changes, the practices of his/her behavior change, as well as new ones arise under the influence of emerging social phenomena. The article considers the views of students about selfies; it defines types of selfies in different categories. It is revealed that preference is given to individual selfies, on holidays or events that are important for the author personally, in order to capture their emotions. It is revealed that almost half of students have a low degree of activity in accounts and is expressed in monitoring the publications of other users.